Visfatin as a Biomarker for Early Detection of Gestational Diabetes Mellitus - Syed Bakht Ruidar, Mazhar Mushtaq, Syed Ali Raza, Farhana Mukhtar, Talha Rehman, Wang Ning, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current study aims to determine whether an increase in visfatin level resulted in Gestational Diabetes Mellitus (GDM) in pregnant females. Study Design: Retrospective Study Place and Duration: Department of Medicine, Dr. Ziauddin Hospital, North Nazimabad, Karachi, From November 2021 to April 2022. Methods: In this study, 83 pregnant females aged 18-46 years were inducated. After obtaining informed written consent, detailed demographic data were recorded. Gestational age and gravidity among all females were recorded. Previous history and frequency of GDM were assessed. Blood samples were taken to determine the concentration of visfatin and glucose levels. SPSS 24.0 was used to analyze all data. Results: In this study, the mean age was 29.11±8.42 years, and the mean BMI was 26.2±3.32 kg/m2. The mean gestational age was 34.11±4.33 weeks. Most of the cases were from rural areas and had poor socio-economic status. We found that 44 (53.01%) subjects had gestational diabetes mellitus while 39 (46.9%) had no diabetes. The visfatin level in patients with gestational diabetes was higher, 4.2±7.124, compared to non-diabetes cases, 1.4±1.432, with a p-value<0.003. Conclusion: Ultimately, we determined that visfatin levels were considerably elevated in gestational diabetes mellitus beginning in the first trimester of pregnancy. An innovative biomarker for GDM detection is increased visfatin levels during pregnancy. Keywords: Visfatin, Gestational Diabetes, Pregnant Females